Quality Control System in the Implementation of High-Rise Building Construction Projects - Ummi Chasanah; Soehartono Soehartono (SEAN Institute, 2026)
System supervision quality project construction is the part that focuses on the process of directing, controlling, in implementation achievement results related construction with target quality project construction. System management quality which is quality plan with identification quality project required construction. So that implementation project construction in documentation during implementation ongoing projects ongoing with objective for reach quality construction as required. Supervision quality construction done to produce appropriate construction required quality in plan construction. In order to fulfill hope owner and maintain quality construction in the field project construction, so that the results obtained in accordance with plan. Implementation efforts project construction in frame for get standard quality from provider services. Parties contractor must can carry out quality in accordance with quality plan, so that results quality in accordance with condition plans and sni. The purpose of study this is for know supervision quality construction in building construction in a way general and specific development uin maulana malik ibrahim malang building. Research this done with method interviews, observations, and the use of bim (building information modeling).